How Can Learning Motivation and Problem-Solving Predict the Mathematical Disposition of Primary Students? - Anggraeni, Uswatin; Amir, Mohammad Faizal; Wardana, Mahardika Darmawan Kusuma (Jurnal Prima Edukasia, 2025)
This study aims to analyse the simultaneous impact of learning motivation (affective aspect) and problem-solving (cognitive aspect) on the mathematical disposition of primary students. Using a quantitative survey with a cross-sectional design, data were collected from 81 fourth-grade students through validated questionnaires and problem-solving tests. Multiple linear regression was applied after verifying the classical assumptions. The results indicated that both variables significantly affect mathematical disposition when analysed together. However, only problem-solving showed a significant partial effect. This suggests that cognitive skills are more dominant than affective factors in shaping students’ mathematical disposition. These findings highlight the importance of strengthening problem- solving skills from an early age as a foundation for developing positive attitudes toward mathematics. The study contributes to theoretical development by integrating cognitive and affective dimensions and offers practical implications for enhancing learning strategies in primary education.